Enhancing survey participation: Facebook advertisements for recruitment in educational research*. Issue 3 (27th May 2018) - Forgasz, Helen; Tan, Hazel; Leder, Gilah; McLeod, Amber
ABSTRACT: Surveys are commonly used to determine how people feel about a specific issue. The increasing availability of the internet and popularity of social networking sites have opened up new possibilities for conducting surveys and, with limited additional costs, enlarge the pool of volunteer respondents with the desired background, experience, or characteristics. In this paper, three different educational research studies are described. In each, a Facebook advertisement was among the methods used for recruitment of survey participants. In two of the studies, Facebook advertising was adopted to overcome obstacles encountered when more traditional sampling procedures failed; in the third study, Facebook was used to broaden representation to include international participants within project budget limitations. Details of the studies and of the recruitment approaches adopted, and the effectiveness of using Facebook advertising are presented. The limitations of using Facebook as a source of recruitment are also considered.